Avaliação da cor de resinas compostas em meios e tempos de armazenamento distintos usando dois espectrofotômetros - Diesel, Pâmela Gutheil (2011)
The aim of this study was to evaluate the color of composite resins when stored in water and red wine, during different periods (immediately after polymerization, 24 hours, 30 days and 180 days) comparing the two measurements of spectrophotometers (Easyshade - Vita and SP60 - X-Rite). Four resin composites were used in two opacities (dentin and enamel): Filtek Supreme XT, Ice, and Opallis Brilliant. After confection 14 specimens (sp) for each resin composite using a metal matrix with 10 mm diameter and 2 mm thick, light cure with a LED (±800mW/cm2) by 40s, sp were polished with Sof-Lex Pop On and felt disc with diamond paste, washed with water and dried with gauze. Immediately after polishing, the initial measurement of the sp was performed, using the CIE L * a * b *. The sp of each composite resin were divided into two groups (n = 7) according to the storage media. Successive readings were taken at 24h, 30 days and 180 days. The color change (ΔE) was calculated using the formula ΔE = ((ΔL)2 + (Δa)2 + (Δb)2)½. The data were subjected to Student t Test and Pearson Linear Correlation for comparison of two spectrophotometers, and ANOVA and Tukey (5%) for each spectrophotometer. In both spectrophotometers, the resins immersed in red wine showed greater change than those kept in water and these values increased over time for most resins. For ΔE obtained by the SP60, the sp immersed in water remained stable, contrary to what was measured by Easyshade that had color changes over time. Although the values of ΔE measured at Easyshade and SP60 were significantly different, they were highly correlated.